Report from the 26th Annual Western Canadian Gastrointestinal Cancer Consensus Conference on Hepatocellular and Biliary Tract Cancer, Saskatoon, Saskatchewan, 17–18 October 2024 - Deepti Ravi; Shahid Ahmed; Blaire Anderson; Brady Anderson; Bryan Brunet; Haji Chalchal; Arun Elangovan; Georgia Geller; Vallerie Gordon; Branawan Gowrishankar; Edward Hardy; Mussawar Iqbal; et al. (Current Oncology)
The 26th annual Western Canadian Gastrointestinal Cancer Consensus Conference (WCGCCC) was held in Saskatoon, Saskatchewan, on 17–18 October 2024. The WCGCCC is an interactive multidisciplinary conference that was attended by healthcare professionals from across Western Canada (British Columbia, Alberta, Saskatchewan, and Manitoba) who are involved in the care of patients with hepatocellular and biliary tract cancers. Specialists from the fields of medical and radiation oncology, interventional radiology, pathology and laboratory medicine, and general and hepatobiliary surgery participated in presentations and discussions for the purpose of developing the recommendations presented here. This consensus statement addresses current issues in the management of hepatocellular and biliary tract cancers.